THE ROLE OF HEAD TEACHERS IN IMPLEMENTATION OF INCLUSIVE EDUCATION IN PUBLIC PRIMARY SCHOOLS IN KALOLENI - RABAI SUBCOUNTIES, KILIFI COUNTY. - ANDAI, DR. STEPHEN OLUTEYO; MWATELA, MAKONDE WESLEY (IJRDO- Journal of Educational Research, 2017)
Development of inclusive education remains one of the major challenges facing educationsystems throughout the world. The purpose of this study was to assess the role of head teachersin implementation of inclusive education in public primary schools in Kaloleni - Rabai SubCounties,Kilifi County. The study objectives were to;examine the head teachers’ role ofsupervision of curriculum in the implementation of inclusive education,assess head teachers’procurement role in implementation of inclusive education, examine head teachers’ financialmanagement role in the implementation of inclusive education, and to examine the headteachers’ role of teacher management in inclusive education in public primary schools inKaloleni - Rabai Sub-Counties. It was premised on Systems Approach Theoryand Theories ofInclusive Education. The study adopted a descriptive survey research design. The targetpopulation was 18 public primary schools, 18 head teachers and 252 teachers in Kaloleni - RabaiSub-Counties. A probability sampling techniques using purposive sampling method wasused toselect the schools for the study. A sample size of 72 teachers and 18 head teachers were selectedyielding to a total of 90 respondents in the study locale. Data was collected using an oralinterview for 18 head teachers and a structured questionnairesfor 72 teachers and an observationchecklist. The questionnaires were validated through appraisal from the supervisors andeducation administration experts from the faculty of education and social sciences and thensubjected to a pilot study. The reliability of the instruments was tested during the pilot study bytesting-retest of the instruments. Descriptive statistics using means mode and frequencieswithsome inferential statistics were employed to analyse the data using Statistical Package for SocialScience (SPSS) programme version 22. The major study findings revealed that implementationof inclusive education has not been accompanied by effective supervision of the curriculum andprocurement of adequate teaching / learning resources from the head teachers in Rabai andKaloleni Sub- Counties in Kilifi County. The study recommends that head teachers to attainhigher qualification to enhance their management capabilities and Ministry of Education toprovide capacity building for all head teachers with inclusive education / financialmanagementskills to enable them effectively undertake their roles of managing schools and toorganise for induction programs / workshops / courses for all head teachers and teachers tofacilitate them on how to handle SNE learners. The government to employ more SNE teachers,increase more funding to schools to cater for SNE learners and to put in place mechanisms ofaccountability and quality control of school funds meant for special education. Finally, the studysuggested further research on assessment of head teachers’ role in supervision of curriculum in inclusive education, effectiveness of head teachers’ in implementation of inclusive education anda replicate of the same study in other counties in Kenya.